First-morning urinary melatonin and breast cancer risk in the guernsey study - Wang, X; Tipper, S; Appleby, P; Allen, N; Key, T; Travis, R (2014)
It has been hypothesized that suppressed nocturnal melatonin production is associated with an increased risk of breast cancer, but results from several small prospective studies of the association have been inconclusive. We examined the association between nocturnal melatonin and breast cancer risk in a case-control study nested within the Guernsey III Study, a British prospective cohort study (1977-2009). Concentrations of 6-sulfatoxymelatonin were measured in prediagnostic first-morning urine samples from 251 breast cancer cases and 727 matched controls. Conditional logistic regression models were used to calculate odds ratios for breast cancer in relation to 6-sulfatoxymelatonin level. No significant association was found between 6-sulfatoxymelatonin level and breast cancer risk, either overall (for highest third vs. lowest, multivariable-adjusted odds ratio = 0.90, 95% confidence interval: 0.61, 1.33) or by menopausal status. However, in a meta-analysis of all published prospective data, including 1,113 cases from 5 studies, higher 6-sulfatoxymelatonin levels were associated with lower breast cancer risk (for highest fourth vs. lowest, odds ratio = 0.81, 95% confidence interval: 0.66, 0.99). In summary, we found no evidence that 6-sulfatoxymelatonin level in a first-morning urine sample was associated with breast cancer risk among British women. However, overall the published data suggest a modest inverse association between melatonin levels and breast cancer risk. Further data are needed to confirm this association. © 2014 © The Author 2014.